Constitutive Laws of Viscoplasticity in Dynamic Response of Structures - Woźnica, K.; Kłosowski, P. (Engineering Transactions, 1997)
The aim of the paper is to discuss the differences which appear in elasto-viscoplastic dynamic analysis of structures using different types of constitutive equations. Three types of constitutive laws are examined: Chaboche, Perzyna and Bodner–Partom models. Material data were taken for calculations from literature. It is shown that for a wide range of strain rates, these different sets of laws produce different functions of yield limit, even for the same material and the same constitutive formulation. Their choice has a large influence on the calculus of dynamic behaviour of structures, where during the deformation process, the strain rates change their values very much. On the other hand, different considerations of hardening in constitutive rules induce also significant differences in dynamic response of viscoplastic structures. We give examples where the published results of experimental investigations in different laboratories lead even to contradictory effects. The authors propose some sets of material parameters which improve the dynamic results and allow to compare the calculated vibrations with different constitutive laws.